DISCOVERY OF THE FIRST SUPER-LITHIUM RICH BEAT CEPHEID: V371 PER - Kovtyukh, V. V.; Gorlova, N. I.; Hillen, M. (Одеські астрономічні публікації, 2012)
Four high-resolution spectra of the double-mode Cepheid V371 Per, obtained for the first time, showed the presence of the abnormally strong Li i 6707.76 Å line. Our analysis of the light element abundances indicates that the star did not go through the evolutionary dredge-up stage. Large distance from the galactic plane and the low metallicity suggest that V371 Per may belong to the thick disc (or to the halo) of the Galaxy, which is consistent with its low metallicity [Fe/H]=-0.42 and the enhancement of the α- and s-elements relative to iron. Line splitting is observed in one of the spectra, which can be due to the non-radial pulsations.